Pengaruh Maintenance Reminder Appointment terhadap Retensi Pelanggan Layanan Servis di Auto2000 Pasteur - Annisa Leni Amalia; Abdul Malik Sayuti; Restu Alam Paripurnawaty (Pusat Riset dan Inovasi Nasional, 2026)
The automotive industry is currently challenged to maintain long-term relationships with customers by implementing effective after-sales service strategies that are oriented toward customer satisfaction. One of the most widely implemented strategies is the Maintenance Reminder Appointment, a periodic vehicle maintenance reminder system designed to encourage customers to have their vehicles serviced according to the manufacturer's recommendations. Auto2000 Pasteur has implemented this strategy to increase customer return visits while strengthening customer retention in its service operations. However, the rate of customer repeat visits still requires optimization to support business sustainability and maintain the company's competitiveness amid the increasingly competitive automotive industry. This study aims to analyze the effect of Maintenance Reminder Appointment on customer retention in the service department of Auto2000 Pasteur. The research data were collected from 352 respondents selected using a purposive sampling technique. This study employed a quantitative descriptive approach, and the data were analyzed using descriptive analysis and the Spearman Rank correlation test. The results indicate that Maintenance Reminder Appointment has a significant effect on customer retention, contributing 61.2%.